ARTEFAK LOGAM DARI SITUS BUTON, SULAWESI TENGGARA ARTI PENTINGNYA BAGI KEKUASAAN MASA KESULTANAN BUTON - Sarjiyanto (Berkala Arkeologi, 2000)
It can be said that the discovery of metal artifacts, especially those related to war equipment, shows that Buton has economic potential as well as a strategic position. This situation then encourages outsiders to attack and try to control them. The consequences of the war later helped determine the political policies of the Buton government, especially in the defense aspect. As a government institution, although the Sultanate of Buton might be less important internationally, but in terms of the development of Islamic culture in the archipelago, it has an important meaning. The Sultanate of Buton is proven to continue to exist with its various dynamics from 1538-1960.